Overview of Family Support and Medication Compliance for Pulmonary TB Patients at the Limboto Health Center - Melisafitri Paramata; Zuriati Muhamad; Rona Febriyona (Universitas Muhammadiyah Palu, 2026)
Pulmonary tuberculosis (TB) is an infectious disease that is still a public health problem and requires long-term treatment so that patient compliance in taking medication is very important to achieve the success of therapy, where one of the factors that can affect patient compliance in undergoing treatment is family support provided during the treatment process. This study aims to describe the picture of family support and medication adherence in pulmonary TB patients at the Limboto Health Center, Gorontalo Regency. This study uses a quantitative method with a descriptive design carried out on pulmonary TB patients at the Limboto Health Center by collecting data using family support questionnaires which include emotional support, awards, information, and instrumentals as well as medication compliance questionnaires which are then analyzed using univariate analysis to describe the distribution of each research variable. The results showed that most of the respondents received good family support, namely 33 respondents (70.2%), while respondents who did not receive family support were 14 respondents (29.8%), and most of the respondents were in the compliant category in undergoing pulmonary TB treatment, namely 43 respondents (91.5%), while respondents who did not comply were 4 respondents (8.5%). Conclusion: Based on the results of the study, it can be concluded that the majority of pulmonary TB patients at the Limboto Health Center have family support and are obedient in taking medication during treatment.